Evaluation of endocervical curettage (ECC) in colposcopy for detecting cervical intraepithelial lesions - Behrens, Annika; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Koch, Martin C.; Schulmeyer, Carla; Seibold, Anja; Gaß, Paul; et al. (Archives of Gynecology and Obstetrics, 2024)
Purpose: Diagnostic challenges in colposcopy arise especially in women aged 50 or older, with postmenopausal status and transformation zone type 3 (TZ3). Endocervical curettage (ECC) is a valuable tool for diagnosing intracervical lesions. The aim of this retrospective analysis was to evaluate the use of ECC in colposcopy for detecting cervical intraepithelial lesions. Methods: A retrospective study was carried out of colposcopies performed in the certified Dysplasia Unit at Erlangen University Hospital between July 2016 and June 2023. Pap and human papillomavirus (HPV) results were correlated with the histologic findings via ECC, obtained during examinations or surgery. The primary outcome was the rate of accuracy between the colposcopic and histologic findings with regard to cytology, age of patients, and type of transformation zone (TZ). Results: A total of 429 colposcopies in 413 women with histologic samples obtained via ECC were included in the final analysis. In all, 355 women had TZ3. Among patients with TZ3, evidence of high-grade lesions and invasive carcinoma was also found in women with normal or low-grade abnormal cytology. For patients with normal colposcopic findings, cervical intraepithelial neoplasia (CIN) 2 and CIN 3/adenocarcinoma in situ (AIS) were found in 56 patients (16%), and invasive carcinoma was found in four patients (0.1%). Conclusion: This analysis suggests that ECC is a valuable tool in the diagnosis of cervical intraepithelial neoplasia, especially for patients who present with a normal colposcopy of the cervix and vagina but have either recurrent abnormal cytologic findings or high-grade abnormal cytology indicating CIN 2 +.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Cervical cancer; Cervical cancer screening assessment; Cervical intraepithelial neoplasia; Colposcopy; Cytology; Endocervical curettage

Impact of the Corona Pandemic on Cervical Cancer Screening Assessment - Stübs, Frederik; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Koch, Martin C.; Mehlhorn, Grit; Beckmann, Matthias; Theuser, Anna Katharin; Schulmeyer, Carla; et al. (In Vivo, 2024)
BACKGROUND/AIM: The global impact of the COVID-19 pandemic resulted in disruptions to healthcare systems throughout the world. The numbers of cytology examinations, human papillomavirus (HPV) tests, and women referred for colposcopy decreased in many countries. There have been no reports on cervical cancer screening in Germany. This study aimed to describe changes in the numbers of colposcopies, cytology examinations, HPV tests, and histological results during the pandemic compared to the pre-pandemic years in order to evaluate the impact of the COVID-19 pandemic on cervical cancer screening. PATIENTS AND METHODS: The numbers of colposcopies, cytology examinations, HPV tests, and histologic results were analyzed retrospectively for the period January 2018 to December 2022. The 2 years period before the pandemic (2018 and 2019) were compared with the 3 years period of the pandemic (2020-2022). RESULTS: In total, 6,518 colposcopies were performed in 5,579 women. The numbers of colposcopies, cytology examinations, and high-risk HPV (hrHPV) tests increased during the pandemic years. The number of biopsies per year taken was stable (range=450-554). The relative numbers of cervical intraepithelial neoplasia (CIN) III/HSIL findings were stable, while the numbers of cervical cancers identified increased slightly from 15 (6.6%) in 2018 to 22 (7.4%) in 2022. CONCLUSION: Increases in numbers of women examined and colposcopies were observed in the years 2021 and 2022 during the pandemic, in comparison to the preceding years. These also led to increases in the figures for cytology, hrHPV, histology, and operations. The onset of the pandemic occurred in the same year as a newly organized screening program started in Germany. The increases might therefore be due to the newly organized screening system.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cervical cancer; cervical cancer screening; cervical dysplasia; COVID-19 pandemic; High-grade squamous intraepithelial lesion (HSIL)

Kolposkopie der Vulva: Wann, wie, wie oft? - Behrens, Annika; Beckmann, Matthias; Gaß, Paul; Schulmeyer, Carla; Seibold, Anja; Dietl, Anna; Stübs, Frederik (gynäkologische praxis, 2025)
Various changes can occur in the vulvar region, which can be of inflammatory origin or caused by autoimmune diseases but can also represent precancerous lesions and invasive carcinomas. Many of these changes are accompanied by symptoms of itching or pain but can also be completely asymptomatic. On the basis of the G-BA diagnostic algorithm, there are no specific recommendations for the use of colposcopy in the evaluation of abnormal vulvar findings. A detailed history of symptoms and knowledge of the physiological anatomy are particularly important. An initial assessment is always performed as part of the cancer screening examination. In the context of further diagnostics, colposcopy of the vulva with targeted histological sampling is helpful. Depending on the diagnosis, various therapeutic procedures are available. The follow-up intervals of HSIL of the vulva are not uniformly regulated and should be adapted to the individual patient‘s risk and the existing disease. Especially in in patients with a history of vulvar HSIL, lifelong follow-up is indicated, whereas vulvar carcinoma is followed up regularly for 5 years.
CRIS-Team Scopus Importer:2025-01-31
Keywords: carcinoma; colposcopy; dysplasie; vulva; vulvar cancer